2018
DOI: 10.1063/1.5022558
|View full text |Cite
|
Sign up to set email alerts
|

Detailed characterisation of focused ion beam induced lateral damage on silicon carbide samples by electrical scanning probe microscopy and transmission electron microscopy

Abstract: The lateral damage induced by focused ion beam on silicon carbide was characterized using electrical scanning probe microscopy (SPM), namely, scanning spreading resistance microscopy and conductive atomic force microscopy (c-AFM). It is shown that the damage exceeds the purposely irradiated circles with a radius of 0.5 lm by several micrometres, up to 8 lm for the maximum applied ion dose of 10 18 cm À2. Obtained SPM results are critically compared with earlier findings on silicon. For doses above the amorphiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In contrast, a study of nanoindentation on SiC coating (59-μm thick) [27] showed an increased hardness and elastic modulus after irradiation, which was attributed to the irradiation-induced point defects that impeded the movement of dislocations. In this study, the observed behaviour at lower loads (1 to 3 mN) was most likely due to Ga ion implantation on the surface [28,29], which hardened the surface layer of the material by obstructing dislocation movement.…”
Section: Lower Load Levelmentioning
confidence: 70%
“…In contrast, a study of nanoindentation on SiC coating (59-μm thick) [27] showed an increased hardness and elastic modulus after irradiation, which was attributed to the irradiation-induced point defects that impeded the movement of dislocations. In this study, the observed behaviour at lower loads (1 to 3 mN) was most likely due to Ga ion implantation on the surface [28,29], which hardened the surface layer of the material by obstructing dislocation movement.…”
Section: Lower Load Levelmentioning
confidence: 70%
“…Phase transformation during or after micro/nano-machining has been widely reported, including micro/nano-cutting [ 67 ], micro/nano-indentation [ 4 ], micro/nano-scratching [ 5 ], Focused Ion Beam (FIB) machining [ 68 ] and so on. Phase transformation characterization and identification is of great significance for understanding material removal mechanism.…”
Section: Raman Spectroscopy Characterization In Micro/nano-machinimentioning
confidence: 99%
“…The main reason is that the beam tails of the FIB significantly damage the area outside the intentionally implanted area. 41, 42 Moreover, the surface in the 2 and 4 regions might be covered with some re-deposition material induced by FIB implantation and sputtering. Rubanov et al 17 proved that the re-deposition material induced by FIB machining is amorphous.…”
Section: Resultsmentioning
confidence: 99%